REAKSI PASAR MODAL TERHADAP PENGUMUMAN PAKET KEBIJAKAN EKONOMI XVI (Studi Empiris Pada Saham Perusahaan Yang Masuk Dalam Indeks LQ 45) - Rante, Tirsa; Falah, Syaikhul; Pangayow, Bill J.C (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2020)
This study aims to analyze whether there are significant differences in abnormal returns before andÂ after the announcement of economic policy XVI and trading volume activity before and after theÂ announcement of XVI economic policy on November 16, 2018. This study uses event study, whereÂ observations of the average abnormal return are carried out. and the average trading volume activity during the 11 day observation period. In this study data was obtained from the Indonesia StockÂ Exchange. The data used in this study include daily closing stock prices (closing price), daily stockÂ trading volume, and the number of shares outstanding. The sample used amounted to 45 LQ45 indexÂ companies. The results of this study indicate (1) there is no significant difference in abnormal returnsÂ before and after the announcement of economic policy XVI (2) on the trading volume activity indicatorÂ there are significant differences before and after the announcement of XVI economic policy.